THROMBOPHILIA AND ABNORMAL LOCATION OF PLACENTA - V. B. Zubenko (Акушерство, гинекология и репродукция)
The aim of the study was to search for a connection between the abnormal location of placenta and the presence of genetic and acquired forms of thrombophilia.Materials and methods. A total of 132 women with the aggravated obstetrical history were examined: Group 1 – 42 patients with the history of placenta previa; Group 2 – 60 pregnant women diagnosed with placenta previa in the current pregnancy; Group 3 – 30 pregnant women with the history of placenta previa and the same abnormality in the current pregnancy. The control group included 120 women with no abnormalities in their obstetric history and with normal location of placenta during the current pregnancy. All patients were assessed for the antiphospholipid antibodies using an enzyme immunoassay. The presence of genetic forms of thrombophilia was tested (with polymerase chain reaction and three pairs of oligonucleotide primers) for the following mutations: the C677T mutation in the 5,10-methylenetetrafolate reductase gene, the prothrombin mutation in the G20210A gene, mutations in the Leiden factor V gene, polymorphism 675 4G/5G in the gene of the inhibitor of plasminogen activator type 1, polymorphism 455G/A in the fibrinogen gene.Results. The thrombophilia spectrum in patients with placenta previa during the current pregnancy and those with abnormal placenta location in the past did not significantly differ from each other. However, in patients with both abnormal placental locations in the past and the present pregnancy, there was a greater occurrence of both genetic and acquired forms of thrombophilia. In the control group, much fewer cases of either genetic or acquired thrombophilia were found.Conclusion. The obtained results suggest a connection between thrombophilia and the abnormal location of placenta. Women with the abnormal placenta location either in the past or during the current pregnancy should be routinely tested for the genetic markers of thrombophilia and for hemostasis abnormalities.